Infrared measurements of total nitrous oxide at Tsukuba - Muramatsu, Hisafumi; Makino, Yukio; Hirota, Michio; Sakaki, Tohru (1984)
P(論文) From measurements of transmittance in the 3.9 μm band (2525-2600(cm)^<-1>) of N_2O to solar radiation, the equivalent width is obtained. Combining these measurements with calculations using a one-layer model, the total amount of N_2O in a vertical column is estimated to be 6.48×(10)^<18> molec. (cm)^<-2>. A simpler method using the transmittances at 2554.6 and 2575.0(cm)^<-1> gives practically the same result for the total amount of N_2O. departmental bulletin paper